Los huérfanos del jihād. Jihād, estrategias de identidad y transformación hacia la no-violencia en la ṭarīqa Tijāniyya en Senegal - de Diego González, Antonio (El Colegio de México, 2017)
This paper explores the concept of jihād, and the strategies of identity and non-violent resistance in ṭarīqa Tijāniyya —one of the most important Sufi organizations of Africa— during colonial era in Senegal. Starting with al-Fūtī’s military defeat, this paper demonstrates the transition from military jihād to non-violent resistance against French authorities in West Africa. In this context, it analyzes he social and intellectual contributions of Mālik Sy and 'Abdoulaye Niasse, leaders of the Ti jāniyya in early XX century. Both, heirs of jihād culture, developed new strategies to increase social resistance while rejecting violence.